Unveiling the Confidence of Criminology Practitioners: Delving on Research Knowledge and Attitude - Nayoyos-Refugia, Jennifer; Dalugdog, Wilfredo D.; Dausan, Alrien F.; Villa, Elizabeth Buena (Future Science / FSH-PH Publications, 2024)
This study aims to investigate the level of confidence among criminology practitioners in their research knowledge and attitudes towards research. By examining both aspects, the study seeks to understand how these factors influence overall confidence in engaging with and applying research findings. Furthermore, this descriptive study explores whether there is a significant difference between practitioners' confidence levels related to their research knowledge and their attitudes towards research. Understanding these dynamics is crucial for enhancing the integration of research into criminology practice, thereby improving the effectiveness of interventions and policies. The study utilized a descriptive design having 128 qualified respondents using purposive sampling that answered the self-made questionnaire. Result shows that among the practitioner, academicians have higher level of confidence in terms of research knowledge and attitude. There is a significant difference between the level of confidence relative to research knowledge and attitude. Likewise, the research knowledge of the criminology practitioners has positive relationship among the scope of practice. Hence, the findings suggest that in order to improve the research culture within the field of criminology, a professional development plan might be created to address and cater to all criminology practitioners within the discipline, with guidelines based on the scope of practice under RA 11131.